2019
DOI: 10.1038/s41598-019-55156-0
|View full text |Cite
|
Sign up to set email alerts
|

DAXX mutations as potential genomic markers of malignant evolution in small nonfunctioning pancreatic neuroendocrine tumors

Abstract: Management of localized well-differentiated pancreatic neuroendocrine tumors (panNETs) is controversial and primarily dependent on tumor size. Upfront surgery is usually recommended for tumors larger than 2 cm in diameter since they frequently show metastatic potential, whereas smaller panNETs are generally characterized by an indolent clinical course, with a rate of relapse or metastasis below 15%. To explore whether increased tumor size is paralleled by genomic variations, we compared the rate and the mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
(36 reference statements)
1
26
0
Order By: Relevance
“…The same opinion was hold by Raj et al (17), Park et al (18) as well as Kim et al (19). However, others were in disagreement (10,11,(20)(21)(22). In their report, the mutations found in the ATRX/DAXX genes was significantly correlated with a shortened survival time.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…The same opinion was hold by Raj et al (17), Park et al (18) as well as Kim et al (19). However, others were in disagreement (10,11,(20)(21)(22). In their report, the mutations found in the ATRX/DAXX genes was significantly correlated with a shortened survival time.…”
Section: Introductionmentioning
confidence: 58%
“…A total of 14 studies with 2313 patients (range from 16-561 per study) were assessed in this meta-analysis (1,10,11,(17)(18)(19)(20)(21)(22)(24)(25)(26)(27)(28). Studies included were published from 2011 to 2021.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Another study compared the mutational profiles of PanNEN that were larger than 2 cm (n = 29) or smaller than 2 cm (n = 27). Herein, it was observed that there was a significantly higher mutational burden in tumours >2 cm, the prevalence of DAXX mutations was borderline significantly higher in larger tumours, and DAXX mutations were associated with increased histological grade, relapse after surgery and reduced disease-free survival (Cives et al 2019a).…”
Section: Pancreatic Neuroendocrine Neoplasmsmentioning
confidence: 90%
“…ALT and loss of DAXX/ATRX are associated with decreased DFS (Marinoni et al 2014, Pipinikas et al 2015, Singhi et al 2017, Chou et al 2018, Roy et al 2018, Cives et al 2019, ATRX loss is associated with poorer OS (Chou et al 2018) and DAXX/ ATRX loss is associated with shorted DSS (Marinoni et al 2014). ALT associated with distant metastases in NF-pNETs <3 cm (Pea et al 2020).…”
Section: Prognostic Factor Evidence In Men1-related Nf-pnets Evidence In Sporadic Nf-pnetsmentioning
confidence: 99%
“…Several retrospective cohort studies have assessed the prognostic value of DAXX/ATRX loss and/or ALT positivity in sporadic surgically resected pNETs (nonfunctioning 75-100%) (Jiao et al 2011, Dogeas et al 2014, Marinoni et al 2014, Pipinikas et al 2015, Park et al 2017, Singhi et al 2017, Chou et al 2018, Pea et al 2020, Roy et al 2018, Cives et al 2019, Uemura et al 2019). All but one study (Park et al 2017) found that ALT and/or DAXX/ ATRX loss (IHC) was associated with decreased relapse-, recurrence-or progression-free survival (Marinoni et al 2014, Pipinikas et al 2015, Singhi et al 2017, Chou et al 2018, Roy et al 2018, Cives et al 2019). One study (Chou et al 2018) also found ATRX loss to be associated with poorer OS and in another study (Marinoni et al 2014) DAXX/ATRX loss was associated with shorter DSS.…”
Section: Imaging-related Characteristicsmentioning
confidence: 99%